Stress Inducible Expression of AtDREB1A Transcription Factor in Transgenic Peanut (Arachis hypogaea L.) Conferred Tolerance to Soil-Moisture Deficit Stress - Sarkar, Tanmoy; Thankappan, Radhakrishnan; Kumar, Abhay; Mishra, Gyan P.; Dobaria, Jentilal R. (Frontiers in Plant Science, 2016)
Peanut, an important oilseed crop, is gaining priority for the development of drought tolerant genotypes in recent times, since the area under drought is constantly on the rise. To achieve this, one of the important strategies is to genetically engineer the ruling peanut varieties using transcription factor regulating the expression of several downstream, abiotic-stress responsive gene(s). In this study, eight independent transgenic peanut (cv. GG20) lines were developed using AtDREB1A gene, encoding for a transcription factor, through Agrobacterium-mediated genetic transformation. The transgene insertion was confirmed in (T0) using PCR and Dot-blot analysis, while copy-number(s) was ascertained using Southern-blot analysis. The inheritance of AtDREB1A gene in individual transgenic plants (T1 and T2) was confirmed using PCR. In homozygous transgenic plants (T2), under soil-moisture deficit stress, elevated level of AtDREB1A transgene expression was observed by RT-PCR assay. The transgenic plants at 45-d or reproductive growth stage showed tolerance to severe soil-moisture deficit stress. Physio-biochemical parameters such as proline content, osmotic potential, relative water content, electrolytic leakage and total-chlorophyll content were found positively correlated with growth-related traits without any morphological abnormality, when compared to wild-type. qPCR analysis revealed consistent increase in expression of AtDREB1A gene under progressive soil-moisture deficit stress in two homozygous transgenic plants. The transgene expression showed significant correlation with improved physio-biochemical traits. The improvement of drought-stress tolerance in combination with improved growth-related traits is very essential criterion for a premium peanut cultivar like GG20, so that marginal farmers of India can incur the economic benefits during seasonal drought and water scarcity.